Stabilization Appliance as Treatment Modality for Headache Attributed to TMD - Alexander, Steven; Himawan, Laura Susanti (Indonesia Prosthodontic Association, 2021)
A 25-year-old female visited Universitas Indonesia Specialty Dental Clinic seeking treatment for her migraine headache (HA). With visual analog scale of 8, the pain was so severe that she often fell from motorcycle several times and suffered sacro-iliac joint pain due to her loss of balance. Upon presentation she appeared to be physically sound, yet she experienced continuous tinnitus and photophobia that affect her daily routine. Her oral status showed missing tooth 18,28,38,48 with occlusal interference at tooth 22 against 32. Her jaw movement were shown to be restricted during protrusive and laterotrusive movement, with pain in her right masseter muscle upon palpation. Trans-cranial x ray examination showed her condyle position to be inferiorly displaced during bite and relax position. After thorough examination using diagnostic decision tree developed by DC/TMD, she was diagnosed with Headache attributed to TMD. 400mg of Ibuprofen were given three times a day for two weeks and a stabilization appliance (SA) was also fabricated. This SA were indicated to provide patient with optimal and simultaneous tooth contact that promoted stability in patient’s stomatognathic relationship. She was also encouraged to do physical self-regulation regime as well as removal of bad habits that contributed to her TMD. After one year and a half, her migraine condition improved and her mandible functioned within normal limits. It is important to note that temporomandibular joint disorder (TMD) and HA are often found to be a co-morbid condition. These conditions were related by them sharing similar neural pathway that converges into Spinal Trigeminal Nucleus. Treatment using stabilization appliance may show a very slow improvement due to how HA can negatively affects patient’s motivation. It is crucial for operator to provide continual support so that patient could adhere to the treatment planned.